Social justice and citizenship values ​​represent the causes of illegal migration within the social fabric of Algerian society. - zeghina, nawel (Journal of Social Sciences and Humanities, 2021)
This theoretical study is an approach to understand the nature of the relationship between many variables and the extent of their contribution to the act of illegal immigration, by searching for the nature of the relationship between the social actor and society, and the extent of his sense of social justice and how it represents the values of citizenship within the social bond in society, with reference to some features and characteristics of Algerian society The variables in this article have multiplied, because the social phenomenon has a specificity that is intertwined and many variables overlap, and the studied topic acquires its importance due to its connection with reality, as it has become necessary to study it and not ignore its effects, as it reflects the repercussions that constitute a threat Foreshadow the worsening reality, the phenomenon of illegal immigration has increased in a striking way, but in reality it is a symptom of a societal reality, and a defect in social construction, and accordingly, before treating the symptom, the disease must be treated, and therefore this research paper aims to reveal how social justice becomes and represents values Citizenship is one of the causal dynamics of the phenomenon of illegal immigration, by following the descriptive approach, by describing the phenomenon and shedding light on the various variables presented for study, The research paper concluded that social justice and the representation of individuals to the values of citizenship become one of the causes that cause illegal immigration, in the absence of The role of the institutions of socialization and the role of the visual media, and this reflects the disintegration of the social bond in terms of the emergence of individualism, social isolation and other problems, which leads to abandonment and withdrawal and resort to illegal immigration to search for the lost alternative and therefore it is necessary to understand the priorities of the social bond, and the nature of relationships In society in terms of arranging and classifying normative structures and focusing on restructuring the value and moral system, to help the social actor locate within the social fabric by giving meaning to his actions, facing the problem of illegal immigration requires a strategic underline Term requires highlighting the cause of these kinetic factors by focusing on reforms in society, these reforms should be directed to achieve social justice in society and how the attention is by individuals and social reality which supports the values of citizenship in society.